Lithological Constraints on Borehole Wall Failure; a Study on the Pennine Coal Measures of the United Kingdom - Fellgett, Mark W.; Kingdon, Andrew; Waters, Colin N.; Field, Lorraine; Shreeve, James; Dobbs, Marcus; Ougier-Simonin, Audrey (Frontiers in Earth Science, 2019)
Stress-related borehole deformation features have been documented across the UK, most commonly as borehole breakouts and drilling induced tensile fractures. Recent studies using borehole imaging have allowed more detailed investigation of these features and the processes that control their formation. Within the Pennsylvanian Pennine Coal Measures Group (PCM) of the UK borehole imaging has highlighted a disproportionately high number of breakouts occurring within palaeosols located immediately below coal seams. To understand the processes controlling breakout formation, a 10.5 m section of core from the Melbourne 1 borehole, incorporating a typical coal seam / palaeosol sequence, was analysed using multiple techniques including: scanning electron and optical microscopy, X-Ray Fluorescence (XRF), X-ray radiography, Point Load testing, wireline petrophysics and track-based core scanning for physical properties. Strength measurements highlight that breakouts form preferentially in poorly consolidated sediments, with low tensile strength, cross-cut by listric surfaces. The formation and termination of breakouts also corresponds to zones of diagenetic iron mineral growth with a lower propensity to fail. These coincide with greater preservation of sedimentary structures and an increase in the rock’s tensile strength; this intra-unit variation in tensile strength constrains breakout length. This demonstrates that secondary diagenetic processes, including the growth of iron minerals impose, lithological controls on the formation and length of borehole breakouts within the UK PCM.